Using Museum Audio Guides in the Construction of Prosthetic Memory. Issue 1 (19th September 2019) - Bertens, Laura; Polak, Sara
The intimacy and affective impact of the audio guide – and the spoken voice – could make it a suitable medium to represent and construct cultural memory. Research on the relevance of the audio guide in the context of cultural memory has, to the best of our knowledge, not yet been conducted. This article will address this by presenting experimental findings on the impact of two custom-made audio guides on visitors and subsequently examining these within a theoretical framework based on Alison Landsberg's concept of prosthetic memory, as well as Gérard Genette's writings about paratexts . In doing so, the focus is on examining the emotional distances perceived between the audio guide and the object on the one hand and the audio guide and its user on the other, as well as the balance between these two. We show that a close link between object and audio guide can either help emotionally engage the user or feel restrictive. A close connection between audio guide and user may be perceived as misleading but can also involve the user in creating prosthetic memory.